Facies model for a coarse‐grained, tide‐influenced delta: Gule Horn Formation (Early Jurassic), Jameson Land, Greenland. Issue 6 (25th May 2016) - Eide, Christian Haug; Howell, John A.; Buckley, Simon J.; Martinius, Allard W.; Oftedal, Bjørn Terje; Henstra, Gijs A.
Abstract: Tide‐dominated deltas have an inherently complex distribution of heterogeneities on several different scales and are less well‐understood than their wave‐dominated and river‐dominated counterparts. Depositional models of these environments are based on a small set of ancient examples and are, therefore, immature. The Early Jurassic Gule Horn Formation is particularly well‐exposed in extensive sea cliffs from which a 32 km long, 250 m high virtual outcrop model has been acquired using helicopter‐mounted light detection and ranging (LiDAR). This dataset, combined with a set of sedimentological logs, facilitates interpretation and measurement of depositional elements and tracing of stratigraphic surfaces over seismic‐scale distances. The aim of this article is to use this dataset to increase the understanding of depositional elements and lithologies in proximal, unconfined, tide‐dominated deltas from the delta plain to prodelta. Deposition occurred in a structurally controlled embayment, and immature sediments indicate proximity to the sediment source. The succession is tide dominated but contains evidence for strong fluvial influence and minor wave influence. Wave influence is more pronounced in transgressive intervals. Nine architectural elements have been identified, and their internal architecture and stratigraphical distribution has been investigated. The distal parts comprise prodelta, delta front and unconfined tidal bar deposits. The medial part is characterized by relatively narrow, amalgamated channel fills with fluid mud‐rich bases and sandier deposits upward, interpreted as distributary channels filled by tidal bars deposited near the turbidity maximum. The proximal parts of the studied system are dominated by sandy distributary channel and heterolithic tidal‐flat deposits. The sandbodies of the proximal tidal channels are several kilometres wide and wider than exposures in all cases. Parasequence boundaries are easily defined in the prodelta to delta‐front environments, but are difficult to trace into the more proximal deposits. This article illustrates the proximal to distal organization of facies in unconfined tide‐dominated deltas and shows how such environments react to relative sea‐level rise.